1980
DOI: 10.2172/5363642
|View full text |Cite
|
Sign up to set email alerts
|

Functions of an engineered barrier system for a nuclear waste repository in basalt

Abstract: PRELIMINARY REPORT This report contains information of a preliminary nature It is subject to revision or correction and therefore does not represent a final report. It was prepared primarily for internal use within Rockwell Hanford Operations Any expressed views and opinions are those of the author and not necessarily of the Company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Adsorbent materials need to possess certain critical properties to be designated as a getter material. Several investigators have identified a number of important performance characteristics that getter materials should possess for effective deployment in repository environments (Coons et al 1980;Klingsberg and Duguid 1980;Nowak 1980a;Moak 1981;Viani 1999). Viani (1999) provided the most comprehensive list of criteria that can be used to assess the properties of potential getter materials.…”
Section: Getter Propertiesmentioning
confidence: 99%
“…Adsorbent materials need to possess certain critical properties to be designated as a getter material. Several investigators have identified a number of important performance characteristics that getter materials should possess for effective deployment in repository environments (Coons et al 1980;Klingsberg and Duguid 1980;Nowak 1980a;Moak 1981;Viani 1999). Viani (1999) provided the most comprehensive list of criteria that can be used to assess the properties of potential getter materials.…”
Section: Getter Propertiesmentioning
confidence: 99%
“…Several investigators have identified a number of important performance characteristics that getter materials should possess for effective deployment (Coons et al 1980, Klingsberg and Duguid 1980, Moak 2.24 1981, Nowak 1980, Viani 1999. Viani (1999) provided a more comprehensive list of criteria (described below) that can be used to assess the properties of potential getter materials.…”
Section: Getter Propertiesmentioning
confidence: 99%
“…These barriers, e.g., waste form, canister, buffer, overpack, and backfill ( package. The functions of the different barriers envisaged by Coons et al (1980) involve redundancy to prevent or reduce the effects of premature failure of one or more components of the system (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of multiple redundancy in the conceptual waste package is indicated in Table 1 (Coons et al, 1980). After emplacement in the repository, the function of the waste form is to retain the radionuclides; whereas the functions of the canister and remaining engineered barriers vary with time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation